Marine issues: from a scientific, political and legal perspective - Ehlers, Peter; Wolfrum, Rüdiger; Mann-Borgese, Elisabeth (Kluwer Law International, 2002)
The purpose of the papers in this volume is to enhance awareness of the European public, governments, the private sector and academia about the importance of responsible ocean and coastal management based on ocean science
"These essays were first presented at the XXVIII Pacem in Maribus Conference ... in Hamburg, Germany"--P. [4] of cover. - Includes bibliographical references. - Description based on print version record
Keywords: Europe; Electronic books -- Aufsatzsammlung -- Conference proceedings; Konferenzschrift; Verschmutzung; Meer; Europa